Overview of approaches to the study of the power – property model in Soviet Russia of the Stalinist period - Beznin, Mikhail A.; Dimoni, Tatiana M. (Journal of the Belarusian State University. History, 2022)
The article is devoted to the review of approaches to the study of the power – property model in Soviet Russia in the late 1920s – early 1950s. The authors describe the main conclusions of domestic research of both the Soviet and post-Soviet periods, a wide front of scientific developments – in the field of history, economics, oriental studies, etc. In addition, the article presents an overview of the main conclusions of foreign, mainly European, researchers in the study of the model of power and property of the Stalinist period. The authors propose to consider the main institutions of the Russian power-proprietary system (ownership, marketability, planning, money), to study the subjects of proprietary rights, the system of divided property rights, the perception of property relations, etc. The proposed approaches will allow historical science to advance in the development of new research tasks for the study of the economic history of Russia of a unique period that entered science under the name of «Stalinist».
Keywords: Stalinist period; economic development; power; property; research methodology